The Problem of Legal Balance Regarding The Rights and Obligations of Husband and Wife From The Perspective of Misyâr Marriage (Mîtsâqan Ghalîẓa) on Marriage Law - Fatkhul Muin; Ahmad Ahmad; Eki Furqon; Nizla Rohaya (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
In this study focuses on legal issues regarding the balance of rights and obligations of husband and wife in misyâr marriage. Misyâr marriage as a form of marriage in which one party promises to release obligations as husband or wife in their marriage, In this marriage model it can result in the non-implementation of the form of marriage prescribed by Islam and state law in the Marriage Law, where the essence of marriage is the physical and spiritual bond of mîtsâqan ghalîẓa (مِيْثَاقًا غَلِيْظًا) between the two parties to live life to become a Sakinâh, mawâdah wa rohmâh family. In the legal and sociological approach to society, that in marriage the essence of the parties carrying out their rights and obligations as husband and wife, so that the balance in marriage. Law No. 1 of 1974 concerning Marriage which emphasizes the nature of marriage on the rights and obligations between the parties, so that, the rights and obligations cannot be released without a reason, while in misyâr marriage, releasing one of its obligations without a sharia reason. In Indonesian society in general, in order to maintain balance, Sighat Ta'liq is often used as a basis for maintaining the relationship between husband and wife in order to maintain balance in the existing marriage, so that the goal of marriage that is Sakinâh, mawâdah wa rohmâh, can be achieved if the balance is realized in the representation in the relationship between husband and wife. In this article aims to analyze in depth the misyâr marriage as a form of deliberate release of obligations without a sharia reason. in this study using qualitative methods and legal approaches in this study, where the perspective on the legal framework of mîtsâqan ghalîẓa and the legal paradigm in Islamic law and marriage law.